Geomorphological Structure of Landform Characteristics As A Reference for Development Recommendations in Active Volcanic and Faulting Areas, A Case Study in Kerinci Region, Jambi Province, Indonesia - Utama, Hari Wiki; Mulyasari, Rahmi (Indonesian Journal on Geoscience, 2024)
Kerinci Regency is located on the western to the southwestern part of the capital city of Jambi Province, Indonesia. It has interesting geomorphological sites consisting of the physiography of the Barisan Mountain Zone associated with the Sumatran Fault System known as a volcanic-tectonic complex. Geomorphology has an important role in providing information of the landscape in an area. This paper aims to determine the geomorphological characteristics of the area which can provide information regarding disaster mitigation, the direction of land-use innovation, and infrastructure development strategies. This research uses analyses of morphographic, morphometric, morphogenetic, morphoconservation, and morphochronological aspects. Analysis of satellite images and topographic contours is a method used to determine the characteristics of drainage patterns and geological mapping. A significant result of this research is a geomorphological map of Kerinci that divides the area into several geomorphological units, namely volcanic-denudational, karst, structural, volcanic-structural, structural-denudational, and fluvial morphologies. Based on the geomorphological map, the area has a very high potential hazard consisting of volcanic structural landforms, which are Tanco Isolated Hill (TIH), Kerinci Fault Escarpment Undulation (KFEU), Kerinci Fault Escarpment Volcanic Undulation (KFEVU), structural landforms (Alang Structural Valley (ASV), Kumun Fault Hills (KFH), and Pengasih Fault Undulation (PGFU)). This map can be used to design the Standard Operating Procedures (SOP) for regional development in Kerinci.